MEANING PATTERNS AND POTENTIAL FORMS OF HALLE DEADJEKTIVAL VERBS MODEL IN GENERATIVE INDONESIAN MORPHOLOGY - Luthfiani, Elma; Wagiran, Wagiran; Rustono, Rustono (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research is prompted by the facts in the field that are found in deadjectival verbs that have the potential to become words commonly used in spoken and written languages. The form and meaning of the deadjectival verb are accepted in the process of formation through the process of affixation. Research data in the form of sentences in which there are deadjectival verbs. The data source of this research is written text. Data collected using the transfer method. Data analysis was performed using the method of distribution with techniques for direct elements and the equivalent method by using the determinant element technique (PUP) and advanced techniques, namely the equalizing relationship technique (HBS). The results of this study are the pattern of grammatical meaning ?proceed to the conditions mentioned on the basis (causative); grammatical meaning patterns ?in a state / do as stated on the basis'; The pattern of grammatical meaning ?the most is on the basis of?; and grammatical meaning patterns ?target in those conditions on the basis?. Potential forms found are *mencoklat, *menjernih, *mencantik, *melembut, *memahit, dan *menggugup.